Introgression of whitefly (Aleurotrachelus socialis) resistance gene from F1 inter specific hybrids into commercial cassava - Akinbo, Olalekan; Labuschagne, Maryke T.; Fregene, Martin A. (Springer, 2012)
The most widespread disease of economic importance of cassava is caused by whitefly vector, both as a single strain or combination of strains. A B1P2 family was generated from the crosses of an inter-specific F1 hybrid (CW 198-11) as a female parent with a commercial cassava cultivar (MTAI-8) as male parent at CIAT headquarters and evaluated in a high-pressure zone for whiteflies in Colombia. 227 genotypes were scored using a scale ranging from 1 (no leaf damage) to 6 (considerable leaf necrosis and defoliation, sooty mould on mid and lower leaves and young stems). The rest were considered promising. The most promising resistance was for damage ratings below 2 for 17.8% of the genotypes. The availability of the pest resistance genotypes, will serve as a means to combat the problem of CMD in Africa provided that resistance to A. socialis is also effective against B. tabaci with different virus strains that is capable of been introduced.